The Influence of Political Trust on Public Participation in The Regional Head Elections during The Covid-19 Pandemic in Cijulang Village, Cineam District, Tasikmalaya Regency - Dewi, Karina Dianti; Gunawan, Hendra; Widiastuti, Wiwi (Journal of Research in Social Science and Humanities, 2022)
This study examines the influence of political trust and the factors that influence the political participation of the Cijulang Village community in the 2020 regional head election during the pandemic. The theory used to solve the problem formulation is the theory of political belief and the theory of political participation and this research uses a political behavior approach or psychology. This research uses quantitative method. The data collection technique is through primary data obtained from questionnaires or questionnaires with a Likert scale and also from interviews with several sources. Sampling with Multistage Random Sampling stratified random with 5 regional heads. The data analysis technique was analyzed using the SPSS for Microsoft Window program with the Pearson correlation test to determine whether the hypothesis was significant or not. The results of this study, for the political trust variable based on the calculation of SPSS version 16, it is known that 0.913 is greater than 0.202, then the political trust variable instrument is said to be reliable and valid. And the Political Participation variable of 0.789 is greater than 0.202 then the political participation variable instrument is said to be reliable and valid. The results of the SPSS are known to be significant at 000 0.5, which is significant and t "count" is greater with t "table" which is 12.1941.98525. SPSS output shows that the political trust of the community is in the very good category, namely 83.2% and political participation is in the very good category, namely 81.2% and the influence of political trust on political participation is 61%. So Ho is rejected and Hi is accepted. So the hypothesis is that there is a positive influence between political trust on people's political participation. The influence of variable x on variable y is due to two factors, namely institutional and psychological factors. And the factors that influence the political participation of the Cijulang Village community are political awareness, political trust and political education as well as the change from substance to commercial agriculture and the rational choice of voters, namely social assistance from the government.Â Â Abstrak: Penelitian ini mengkaji pengaruh kepercayaan politik dan faktor-faktor yang mempengaruhi partisipasi politik masyarakat Desa Cijulang dalam pemilihan kepala daerah tahun 2020 disaat pandemi. Teori yang di gunakan untuk memecahkan rumusan masalah yaitu teori kepercayaan politik dan teori partisipasi politik serta penelitian ini menggunakan Pendekatan prilaku politik atau psikologi. Penelitian ini menggunakan metode Kuantitatif. Teknik pengumpulan data yaitu melalui data primer yang diperoleh dari angket atau quisioner dengan skala Likert dan juga dari wawancara beberapa narasumber. Pengambilan sample dengan Multistage Random Sampling acak bertingkat dengan 5 kepala wilayah. Teknik analisisis data melalui di analisis menggunakan program SPSS for Microsoft Window dengan uji kolerasi Pearson dengan penentuan hipotesis signifikan atau tidak. Hasil penelitian ini Untuk variabel kepercayaan politik berdasarkan perhitungan SPSS versi 16 diketahui sebesar 0,913 lebih besar dari 0,202 makaÂ  instrumen variabel kepercayaanÂ  politik dikatakan reliable dan valid. Dan variabel Partisipasi Politik sebesar sebesar 0,789 lebih besar dari 0,202 makaÂ  instrumen variabel partisipasiÂ  politik dikatakan reliable dan valid. Hasil dari spss diketahui siginifian sebesar 0000,5 yaitu signifikan dan t"hitung"Â  lebih besar dengan t â€œtabelâ€ yaitu 12.1941.98525. output spss menjukan Kepercayaan politik masyarakat termasuk kategori sangat baik yaitu 83,2% dan partisipasi politik termasuk kategori sangat baik yaitu 81,2% dan pengaruh kepercayaan politik terhadap partisipasi politik yaitu 61%. Maka Ho ditolak dan Hi diterima. Sehingga hipotesis adanya pengaruh positif antara kepercayaan politik terhadap partisipasi politik masyarakat. Adanya pengaruh dari variabel x terhadap variabel y karena adanya dua faktor yaitu faktor institusi dan psikologi. Serta Faktor yang mempengaruhi partisipasi politik masyarakat Desa Cijulang adalah kesadaran politik, kepercayaan politikÂ  dan pendidikan politik serta perubahan dari subtansi menjadi komersial pertanian dan adanya pilihan rasional pemilih yaitu bantuan sosial dari pemeritah.